Statistical Approaching for Superhydrophobic Coating Preparation using Silica Derived from Geothermal Solid Waste - S Silviana; Adi Darmawan; Agus Subagio; Febio Dalanta (Department of Chemical Engineering, Universitas Gadjah Mada, 2020)
Material quality can be affected by humidity resulting in short durability. Many observations have been conducted to endure the durability of material, such as coating methods. However, recent methods are unaffordable. Therefore, this paper observes efficient and effective method to prepare superhydrophobic silica coatings derived from geothermal waste. The method was conducted by spraying. The objective of this paper is to observe optimum condition by using variables of silica concentration, TMCS (trimethylsilyl chloride) concentration, solvents and materials confirmed by contact angle of material based on statistical analysis. The study consisted of silica treatment for purification and preparation of superhydrophobic silica coatings. The study was carried out in factorial design of 81 experiments with one-time replication through Design Expert software (version 8.0.6). Based on previous research, the experiment was obtained optimum condition at 5.5 %w/v, 13 %v/v, isooctane, zinc coated for silica concentration, TMCS concentration, solvent and material, respectively, releasing contact angle by instrumentation of 180°. By ANOVA analysis, it was also complied the optimum condition of the superhydrophobic coating solution preparation achieved the same condition with experimental data releasing contact angle of 179.69°.